Central Bank Autonomy and Price Stability in Sub-Saharan Africa: Implications for the Bank of Central African States (BEAC) (Global Journal of Human-Social Science, 2025)
Abstract not found
Keywords: central bank autonomy; price stability; static panel data; sub-saharan africa (SSA)